Remediation of emerging metal pollutants using environment friendly biochar- Review on applications and mechanism. (March 2022) - Berslin, Don; Reshmi, Angelin; Sivaprakash, Baskaran; Rajamohan, Natarajan; Kumar, P. Senthil
Abstract: Bioremediation of heavy metals has become a major environmental concern due to their bio resistant nature and tendency to accumulate. Application of various technologies, involving physical and chemical working principles are applied and passive uptake using sorption involving eco-friendly substrates gained significant attention. Biochar, a cheaper and efficient material, offers good potential due to the greater ease of production, treatment and disposal. This review focuses on the effective application of biochar to treat water contaminated by three specific heavy metals: chromium, lead and arsenic. The on-field applications like soil amendment, industrial wastewater treatment and groundwater treatment using biochar are highlighted. The review article describes the feedstock available for biochar production, various production processes and the importance of optimum conditions like pyrolysis temperature, rate and retention time for various feedstocks reported in literature. The energy requirement of the production process can be supplied by its own energy output. Various modifications that are suitable for the biochar from distinct feedstocks are also discussed. The removal performance of biochar at different working conditions like pH, initial concentration of pollutant and adsorbent dose are consolidated. The highest removal efficiencies reported were by coconut shell biochar (Cr – 99.9%), canola straw biochar (Pb – 100%) and perilla leaf biochar (As – 100%). The adsorption mechanism is explained with reference to kinetics, isotherms, and molecular dynamics. Adsorption mechanism of most of the biochars was found to fit either Freundlich or Langmuir isotherm. Graphical abstract: Image 1 Highlights: Comprehensive review on biochar application for removal of chromium, lead and arsenic is discussed. Different methods used for biochar modification are discussed. Removal performance of biochar at different working conditions are consolidated. Kinetic, isotherm and molecular dynamic models are reviewed.